1991
DOI: 10.1063/1.460139
|View full text |Cite
|
Sign up to set email alerts
|

An examination of a bi n i t i o results for the helium potential energy curve

Abstract: A b i n i t i o calculations of transition probabilities and potential curves of SiH A b i n i t i o correlated potential energy surfaces for monomeric sodium and potassium cyanides A b i n i t i o SCF calculations on the potential energy surface of potassium cyanide (KCN)Obtaining a ground state potential energy curve for helium has been the subject of much research involving empirical, semiempirical, and ab initio methods. In this work, we examine critically recent ab initio potentials proposed for this inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
332
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(343 citation statements)
references
References 24 publications
9
332
0
2
Order By: Relevance
“…The latter is expected to be small and in the case of the He-He-He system it has been shown to contribute to less than 1% to the ground state energy [25,26]. For the He-He pair interaction, we used the one from Aziz and Slaman [27]. Other newer potentials have been proposed recently [29,30], but they do not differ much from the one employed here.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The latter is expected to be small and in the case of the He-He-He system it has been shown to contribute to less than 1% to the ground state energy [25,26]. For the He-He pair interaction, we used the one from Aziz and Slaman [27]. Other newer potentials have been proposed recently [29,30], but they do not differ much from the one employed here.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…As pointed out by Efimov and Tkachenko [5], for a , LM2M2 [7], HFD-B [8] and HFDBFCI1 [9]. Note the approximately linear relationship (dashed line).…”
mentioning
confidence: 93%
“…The second correction is the introduction of a finite-range parameter, Γ 3 n , depending on the energy level, which produces a shift in the product κ * a B . Recently it has been shown that the value of the shift is almost the same for very different potentials in range and scale as the LM2M2 interaction of Aziz [8], a gaussian potential reproducing the values of E 2 and a given by that interaction and a combination of yukawians, the MT-III interaction [9], describing the s-wave triplet n − p state. Interestingly the value of the shift for the ground state in the three cases results to be almost the same, Γ 3 0 ≈ 0.8 [10].…”
Section: Efimov Plot With 1/2-spin-isospin Fermionsmentioning
confidence: 99%